Differential effect of a continental breakfast on tacrolimus formulations with different release characteristics - Huppertz, Andrea; Bollmann, Johanna; Behnisch, Rouven; Bruckner, Thomas; Zorn, Markus; Burhenne, Jürgen; Haefeli, Walter E.; Czock, David (Clinical pharmacology in drug development, 2021)
Food reduces tacrolimus bioavailability after immediate-release tacrolimus (IR-Tac) and after a new prolonged-release tacrolimus formulation (PR-Tac), when using a high-fat breakfast, but the effects of a continental breakfast on PR-Tac are unknown. In an open-label, 4-phase, randomized, 2-sequence, crossover pharmacokinetic trial, 36 healthy volunteers (18 females) received single 5-mg tacrolimus doses as PR-Tac and as IR-Tac fasted or with a standardized continental breakfast. Tacrolimus pharmacokinetics were analyzed using noncompartmental methods and mixed-model analysis of variance. The continental breakfast significantly decreased average tacrolimus exposure (area under the plasma concentration-time curve) with both preparations (IR-Tac, 67%; 90% confidence interval [CI], 59%-75%; P < .01; and PR-Tac, 79%; 90%CI, 70%-89%; P < .01) with a nonsignificant difference between both preparations (P = .10). The maximum concentration (Cmax) and the time to maximum concentration (tmax) were significantly affected only after IR-Tac (Cmax IR-Tac, 39%; 90%CI, 34%-45%; P < .01; and PR-Tac, 87%; 90%CI, 76%-101%; P = .11; tmax IR-Tac, 212%, 90%CI, 179%-252%; P < .01; and PR-Tac, 101%; 90%CI, 86%-120%; P = .89), which was significantly different between both preparations (P < .01). Considering switching from IR-Tac to PR-Tac, predicted dose requirements differed according to the timing of drug intake in relation to food. In conclusion, a continental breakfast decreased average tacrolimus exposure of both preparations to a similar extent. Cmax and tmax were affected only after IR-Tac. The effect of a standardized continental breakfast on PR-Tac was considerably smaller than previously reported effects of a high-fat breakfast on PR-Tac.